Tenascin-W Is a Novel Stromal Marker in Biliary Tract Cancers - Hendaoui, Ismaïl; Lahmar, Ahlem; Campo, Luca; Mebarki, Sihem; Bichet, Sandrine; Hess, Daniel; Degen, Martin; Kchir, Nidhameddine; Charrada-Ben Farhat, Leila; Hefaiedh, Rania; Ruiz, Christian; Terracciano, Luigi M.; et al. (Frontiers in Immunology, 2021)
Extrahepatic cancers of the biliary system are typically asymptomatic until after metastasis, which contributes to their poor prognosis. Here we examined intrahepatic cholangiocarcinomas (n = 8), carcinomas of perihilar bile ducts (n = 7), carcinomas of the gallbladder (n = 11) and hepatic metastasis from carcinomas of the gallbladder (n = 4) for the expression of the extracellular matrix glycoproteins tenascin-C and tenascin-W. Anti-tenascin-C and anti-tenascin-W immunoreactivity was found in all biliary tract tumors examined. Unlike tenascin-C, tenascin-W was not detected in normal hepatobiliary tissue. Tenascin-W was also expressed by the cholangiocarcinoma-derived cell line Huh-28. However, co-culture of Huh-28 cells with immortalized bone marrow-derived stromal cells was necessary for the formation and organization of tenascin-W fibrils in vitro. Our results indicate that tenascin-W may be a novel marker of hepatobiliary tumor stroma, and its absence from many normal tissues suggests that it may be a potential target for biotherapies.